2019
DOI: 10.1158/0008-5472.can-18-2616
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Remodeling in the Hypoxic Tumor-Mesothelial Niche Promotes Ovarian Cancer Metastasis

Abstract: Peritoneal metastases are the leading cause of morbidity and mortality in high-grade serous ovarian cancer (HGSOC). Accumulating evidence suggests that mesothelial cells are an important component of the metastatic microenvironment in HGSOC. However, the mechanisms by which mesothelial cells promote metastasis are unclear. Here we report that the HGSOC tumor-mesothelial niche was hypoxic and hypoxic signaling enhanced collagen I deposition by mesothelial cells. Specifically, hypoxic signaling increased express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 53 publications
(59 reference statements)
3
91
0
1
Order By: Relevance
“…Targeting CCR1 in cancer patients to reduce metastasis or induce changes in the tumor microenvironment might lead to anti-tumor immune responses due to reduction of monocytic infiltration. 15,17,[50][51][52][53] . Neutrophil Extracellular Traps (NET) formation provides a premetastatic omental niche conducive for implantation of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting CCR1 in cancer patients to reduce metastasis or induce changes in the tumor microenvironment might lead to anti-tumor immune responses due to reduction of monocytic infiltration. 15,17,[50][51][52][53] . Neutrophil Extracellular Traps (NET) formation provides a premetastatic omental niche conducive for implantation of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, mesothelial cells are displaced by ovarian cancer spheroids followed by invasion of cancer cells into the deeper layer of peritoneal tissues 54 . Specifically, hypoxic signaling increased expression of lysyl oxidase (LOX) in mesothelial and ovarian cancer cells to promote collagen crosslinking and tumor cell invasion 52 . Further, during ovarian cancer progression, omental adipocytes provide fatty acids as an energy source to ovarian cancer cells 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Other partners in close contact with collagen involvement in cancer are microRNAs (miRNAs) [125] and exosomes [126]. Moreover, collagen interaction with other ECM molecules including fibronectin, laminin, hyaluronic acid, and MMPs influences cancer cell activity [127]. In addition, hypoxia, which is common in collagen-rich tumors, promotes cancer progression [124].…”
Section: Ecmmentioning
confidence: 99%
“…ECM is composed of collagen, elastin fibrils, proteoglycan, glycosaminoglycan, glycoprotein and protease, which are interconnected to form a dynamic cell regulatory niche and provide structural stability [ 254 ]. Studies have shown that ECM is sustainably remodeled to play an important role in the proliferation, migration, adhesion, invasion and metastasis of tumor cells [ 255 , 256 ]. In intratumoral hypoxia, HIF-1α activates genes encoding collagen prolyl hydroxylases, such as P4HA1 and P4HA2, and collagen prolyl hydroxylases, such as PLOD2 [ 257 ].…”
Section: Role Of Hif-α On Extracellular Matrix Remodeling Through Epimentioning
confidence: 99%